2007
DOI: 10.1093/ije/dyl282
|View full text |Cite
|
Sign up to set email alerts
|

Differential impacts of health care in Australia: trend analysis of socioeconomic inequalities in avoidable mortality

Abstract: Background Recent avoidable mortality trends in Australia suggest that health care has made a substantial contribution to reducing mortality. This study investigates if the benefits of health care have been distributed equally by comparing declines in avoidable with non-avoidable mortality over time by socioeconomic status (SES). MethodsWe calculated avoidable and non-avoidable mortality rates in Australia by small areas for 1986, 1991, 1997 and 2002. We performed pooled cross-sectional trend analysis of indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 39 publications
2
67
0
4
Order By: Relevance
“…The observed widened income-related inequality in deciduous caries experience has added to the recent evidence of divergent trends of health by SES (Mishra et al, 2004;Page et al, 2006;Korda et al, 2007;Blakely et al, 2008). There are several possible reasons for the observed widened inequality in oral health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed widened income-related inequality in deciduous caries experience has added to the recent evidence of divergent trends of health by SES (Mishra et al, 2004;Page et al, 2006;Korda et al, 2007;Blakely et al, 2008). There are several possible reasons for the observed widened inequality in oral health.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of widening socio-economic inequality in Australia that may have a direct impact on the SES gradient in health, including the oral health of children (Hetzel et al, 2004). A widening trend of SES inequality in other aspects of health in this past decade has been reported in Australia (Najman et al, 2006;Korda et al, 2007) and other countries (Mishra et al, 2004;Fawcett et al, 2005;Blakely et al, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…Nonetheless, available information does not generally suggest narrowing of socioeconomic gradients. Analysis by Korda et al (2007) shows that the socio-economic gradient of overall non-age-specific death rates associated with both avoidable and non-avoidable causes increased between 1986 and 2002. Freemantle et al (2006) show that the gap in death rates between Indigenous and non-Indigenous infants increased between 1980 and 2001, even though overall death rates fell in both populations.…”
Section: Discussionmentioning
confidence: 99%
“…Conducted studies have mostly shown that the rate of avoidable deaths by time has declined. As such, their scale and pace with regard to sex, ethnic, age groups and socioeconomic quintiles have been different (7)(8)(9)(11)(12)(13)(14). In Iran over the past three decades, in particular after the establishment of healthcare networks, mortality rate among the provinces has fallen differently and considerably (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%